Brazing process for connecting aluminum oxide ceramic and metallic titanium through low-activation brazing filler metal

By using low-activated aluminum-based solder and advanced process treatment, the radioactivity problems caused by the connection of medium- and high-activated solder of alumina ceramics and metal titanium are solved, achieving higher connection strength and longer equipment service life.

CN119897542AActive Publication Date: 2025-04-29ANHUI XIHE BEAM NEUTRON TECHNOLOGY CO LTD

Patent Information

Application Number
CN202510209566.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-25
Publication Date
2025-04-29
Estimated Expiration
2045-02-25

AI Technical Summary

Technical Problem

The brazing connection between existing alumina ceramics and metal titanium uses highly activated brazing materials, which generates radioactive substances after irradiation, which increases the equipment maintenance cycle and reduces service life.

Method used

Low-activated aluminum-based solder is used to form a nanocrystalline structure and uniformly distributed precipitation phase through magnetron sputtering titanium film and laser microtextured treatment. Combined with gradient heating and alternating magnetic field treatment, the strength and stability of the joint are improved.

Benefits of technology

It effectively reduces the radioactive activity of the solder under irradiation conditions, improves the connection strength and stability of alumina ceramics and metal titanium, and extends the service life of the equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119897542A_ABST
    Figure CN119897542A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of brazing processes, in particular to a brazing process for connecting aluminum oxide ceramic and metallic titanium through low-activation brazing filler metal. According to the technical scheme, the method comprises the following steps that a to-be-welded face of the aluminum oxide ceramic is subjected to magnetron sputtering titanium film plating, the sputtering power ranges from 80 W to 150 W, the argon pressure ranges from 0.5 Pa to 1.5 Pa, the film thickness ranges from 0.5 micrometer to 5 micrometers, inert gas annealing treatment is conducted after film plating, the annealing temperature ranges from 400 DEG C to 550 DEG C, and the heat preservation time ranges from 10 min to 30 min; and the surface of the metal titanium substrate is subjected to laser micro-texture treatment, and a periodic groove structure with the depth being 10-50 microns is formed. The problems of poor wettability of the brazing filler metal and the ceramic, low joint strength and joint stress cracks are solved, meanwhile, radioactive substances generated by the brazing filler metal under the irradiation condition can be released within a short time, the equipment maintenance period is greatly shortened, and the equipment service life is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of brazing technology, in particular to a brazing process for connecting alumina ceramic and metal titanium with a low-activated brazing filler metal. Background Art

[0002] Alumina ceramics are an inorganic non-metallic material with excellent mechanical properties, high temperature resistance, corrosion resistance and electrical insulation properties. They are widely used in high-tech fields such as aerospace, electronics, chemical equipment and medical equipment. Titanium metal also plays an important role in aerospace, chemical industry, marine engineering and biomedicine due to its high specific strength, excellent corrosion resistance and biocompatibility. The combination of alumina ceramics and titanium metal can combine the excellent properties of the two materials and is widely used in high-temperature sensors, electronic packaging, chemical reactors and medical implants.

[0003] Due to the significant differences in physical, chemical and thermal properties between alumina ceramics and titanium metal, including large differences in thermal expansion coefficients, poor wettability, and the easy formation of brittle compounds at the bonding interface, it is difficult to achieve a reliable connection between the two by traditional mechanical bonding or direct fusion welding. These problems limit the application of alumina ceramics and titanium metal in complex working conditions with higher requirements. As an efficient connection method, brazing has become a research hotspot for achieving reliable connection between alumina ceramics and titanium metal due to its advantages such as relatively low operating temperature, simple process and stable joint performance. By selecting appropriate brazing materials and optimizing process parameters, brazing can overcome the wettability barriers between ceramics and metals and form a high-strength metallurgical bond. The connection process of alumina ceramic materials mainly needs to solve two problems: one is the wettability problem of the connection interface; the other is the stress buffering problem of the joint.

[0004] The accelerating tube is a key component of the accelerator. It accelerates the electrons injected from the electron gun to high energy under the action of the microwave electric field, and finally produces high-energy X-rays when hitting the target. Therefore, its working environment is easily irradiated. At present, the brazing connection of alumina ceramics mainly adopts active brazing materials such as Ag-based brazing materials and Cu-based brazing materials to achieve the connection, but it is a highly activated element and will produce radioactive substances after irradiation, which will increase the equipment maintenance cycle and reduce the service life.

[0005] In summary, the present application proposes a brazing process for connecting alumina ceramic and metallic titanium using a low-activated brazing filler metal. Summary of the invention

[0006] The purpose of the present invention is to propose a brazing process for connecting alumina ceramics and metal titanium using low-activated brazing filler metals, in view of the problem that the brazing connection of alumina ceramics in the background technology mainly adopts active brazing filler metals such as Ag-based brazing filler metals and Cu-based brazing filler metals to achieve the connection, which will produce radioactive substances after irradiation, increase the equipment maintenance cycle and reduce the service life.

[0007] The technical solution of the present invention is a brazing process for connecting alumina ceramic and titanium metal with low-activated brazing filler metal, comprising the following steps:

[0008] S1. The surface of alumina ceramic to be welded is subjected to magnetron sputtering titanium coating, the sputtering power is 80-150W, the argon pressure is 0.5-1.5Pa, the film thickness is 0.5-5μm, and after coating, it is annealed by inert gas, the annealing temperature is 400-550℃, and the holding time is 10-30min;

[0009] S2. The surface of the titanium substrate is subjected to laser microtexturing to form a periodic groove structure with a depth of 10-50 μm, and then the oxide film is removed by ultrasonic cleaning using a mixed solution of hydrofluoric acid and nitric acid;

[0010] S3. A low-activated aluminum-based solder having a composition of 96.8-97.65wt.% Al, 2.2-2.8wt.% Mg, 0.15-0.35wt.%, with a purity of ≥99%, and the solder is preformed into a foil having a thickness of 0.02-0.5mm;

[0011] S4. The coated alumina ceramic, the titanium substrate and the brazing foil are assembled in sequence to form a laminated structure of alumina ceramic / brazing material / titanium substrate / brazing material / alumina ceramic, and a preload pressure of 0.5-2MPa is applied;

[0012] S5. Carry out gradient heating in a vacuum brazing furnace: in the first stage, heat to 300-400℃ at 10-15℃ / min, keep warm for 10-20min to eliminate interface stress; in the second stage, heat to 690-790℃ at 5-8℃ / min, keep warm for 2-60min, and the vacuum degree is ≤1×10-3Pa; in the third stage, slowly cool to below 200℃ at 3-5℃ / min and then cool with the furnace.

[0013] Optionally, the protective gas for the inert gas annealing treatment in step S1 is argon or helium, the gas flow rate is 20-50 sccm, and the grain size of the film layer after annealing is 50-200 nm.

[0014] Optionally, in the step S2, the groove pitch of the laser microtexturing is 50-150 μm, and the ratio of the groove width to the depth is 1:1.5-1:3.

[0015] Optionally, in step S3, the surface of the solder foil is doped with 0.01-0.1 wt.% of rare earth element Y or Ce by ion implantation, and the doping depth is 0.1-0.5 μm.

[0016] Optionally, in the step S5, an alternating magnetic field is applied during the heat preservation stage, with a magnetic field strength of 50-200 mT and a frequency of 1-10 kHz.

[0017] Optionally, after the brazing is completed, the joint is subjected to aging treatment, the aging temperature is 150-250° C., the insulation time is 2-8 h, and then cooled to room temperature at a rate of ≤10° C. / min.

[0018] Optionally, the pre-tightening pressure in step S4 is achieved by a shape memory alloy fixture, and the fixture undergoes phase change and shrinkage at the brazing temperature, and the pressure is dynamically adjusted to ±5% of the set value.

[0019] Optionally, the microstructure of the aluminum-based low-activation solder is a nanocrystalline structure, the grain size is ≤100 nm, and Mg2Si and CrAl7 precipitated phases are evenly distributed at the grain boundaries.

[0020] Optionally, in step S2, the volume ratio of the mixed solution is hydrofluoric acid: nitric acid: deionized water = 1:3:6, the ultrasonic cleaning power is 200-400 W, and the time is 5-15 min.

[0021] Optionally, during the gradient heating stage, the interface temperature distribution is monitored in real time by infrared thermal imaging, the temperature uniformity deviation is ≤±5°C, and the heating rate is dynamically adjusted by a feedback system.

[0022] Compared with the prior art, the present invention has at least one of the following beneficial technical effects:

[0023] By magnetron sputtering titanium film on the surface of alumina ceramic to be welded, the wettability of ceramic and solder can be enhanced. After plating, inert gas annealing treatment can refine the film grains and improve the stability and bonding strength of the film. The periodic groove structure formed by laser micro-texturing treatment on the surface of the metal titanium substrate increases the contact area with the solder, improves the mechanical interlocking effect, and enhances the connection strength.

[0024] The aluminum-based low-activation solder with specific composition has a nanocrystalline structure and evenly distributed precipitation phases at the grain boundaries, which improve the strength, toughness and corrosion resistance of the solder; the surface of the solder foil is doped with rare earth elements Y or Ce to further improve the wettability, fluidity and interface reaction of the solder, thereby improving the joint performance.

[0025] The gradient heating method can effectively eliminate interface stress and avoid problems such as material deformation and cracking caused by rapid temperature changes. An alternating magnetic field is applied during the insulation stage to promote the diffusion of solder atoms, improve the uniformity of joint structure, and increase the strength and density of the joint. Infrared thermal imaging is used to monitor the interface temperature distribution in real time and dynamically adjust the heating rate to ensure temperature uniformity and improve the stability of brazing quality.

[0026] The pre-tightening pressure is achieved by using a shape memory alloy fixture, and the pressure can be dynamically adjusted according to demand at the brazing temperature to ensure stable pressure during the brazing process, ensure close contact between the brazing material and the base material, and improve the connection quality.

[0027] The present invention proposes a brazing method for alumina ceramics and titanium metal suitable for reducing the radioactivity of an accelerating tube, which solves the problems of poor wettability of the brazing material and ceramics, low joint strength and joint stress cracks, and can also ensure that the radioactive substances generated by the brazing material under irradiation conditions can be decontrolled in a relatively short time, thereby greatly shortening the equipment maintenance cycle and increasing the service life of the equipment. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 A flow chart of a brazing process for connecting alumina ceramic and titanium metal using a low-activated brazing filler metal;

[0029] Figure 2 This is a microstructure morphology of the interface of the joint of alumina ceramic and titanium metal brazed using low-activation brazing filler metal in Example 1;

[0030] Figure 3 This is a microstructure morphology of the interface of the joint of alumina ceramic and titanium metal brazed using low-activation brazing filler metal in Example 2;

[0031] Figure 4 This is a microstructure morphology of the interface of the joint of alumina ceramic and titanium metal brazed using low-activation brazing filler metal in Example 3;

[0032] Figure 5 This is the microstructural morphology of the interface of the alumina ceramic and metal titanium joint brazed using low-activation brazing filler metal in Example 4. DETAILED DESCRIPTION

[0033] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and specific embodiments.

[0034] Example 1

[0035] like Figure 1 As shown, a brazing process for connecting alumina ceramic and titanium metal with a low-activated brazing filler metal comprises the following steps:

[0036] S1. The surface of alumina ceramic to be welded is subjected to magnetron sputtering titanium coating, the sputtering power is 80W, the argon pressure is 0.5Pa, the film thickness is 0.5μm, and the coating is subjected to inert gas annealing treatment, the annealing temperature is 400℃, the holding time is 10min, the protective gas for inert gas annealing treatment is helium, the gas flow rate is 20sccm, and the grain size of the film layer after annealing is 50nm;

[0037] S2. The surface of the titanium substrate was subjected to laser microtexturing to form a periodic groove structure with a depth of 10 μm, and then the oxide film was removed by ultrasonic cleaning using a mixed solution of hydrofluoric acid and nitric acid. The groove spacing of the laser microtexturing was 50 μm, and the ratio of the groove width to the depth was 1:1.5. The volume ratio of the mixed solution was hydrofluoric acid: nitric acid: deionized water = 1:3:6, the ultrasonic cleaning power was 200 W, and the time was 5 min.

[0038] S3. Aluminum-based low-activation solder is used, whose composition is Al 96.8wt.%, Mg 2.2wt.%, Cr 0.15wt.%, and the purity is ≥99%. The solder is prefabricated into a foil with a thickness of 0.02mm, and the surface of the solder foil is doped with 0.01wt.% of rare earth element Y by ion implantation, and the doping depth is 0.1μm; the microstructure of the aluminum-based low-activation solder is a nanocrystalline structure, the grain size is ≤100nm, and the Mg2Si and CrA l7 precipitation phases are evenly distributed at the grain boundaries;

[0039] S4. The coated alumina ceramic, the metal titanium substrate and the brazing material foil are assembled in sequence to form a laminated structure of alumina ceramic / brazing material / titanium substrate / brazing material / alumina ceramic, and a pre-tightening pressure of 0.5 MPa is applied. The pre-tightening pressure is achieved by a shape memory alloy fixture. The fixture undergoes phase change and shrinkage at the brazing temperature, and the pressure is dynamically adjusted to ±5% of the set value;

[0040] S5. Gradual heating is carried out in a vacuum brazing furnace: in the first stage, the temperature is increased to 300°C at 10°C / min and kept at this temperature for 10-20min to eliminate interface stress; in the second stage, the temperature is increased to 690°C at 5°C / min and kept at this temperature for 2min, and the vacuum degree is ≤1×10-3Pa; in the third stage, the temperature is slowly cooled to below 200°C at 3°C / min and then cooled with the furnace. During the holding stage, an alternating magnetic field is applied with a magnetic field strength of 50mT and a frequency of 1kHz.

[0041] After brazing, the joint was aged at 150 °C for 2 h, and then cooled to room temperature at a rate of ≤10 °C / min. Figure 2 As shown, there are no cracks;

[0042] During the gradient heating stage, infrared thermal imaging is used to monitor the interface temperature distribution in real time, with the temperature uniformity deviation ≤±5°C, and the heating rate is dynamically adjusted through a feedback system.

[0043] In the process of gradient heating in the vacuum brazing furnace, an adaptive control algorithm is introduced, as follows:

[0044] Data collection: Use an infrared thermal imager to collect interface temperature distribution data at a frequency of once per second to obtain temperature values ​​at multiple temperature measurement points.

[0045] Comparison judgment: Compare the collected temperature of each temperature measurement point with the preset temperature uniformity deviation range (≤±5℃). If the temperature of a certain point deviates from the set temperature by more than 5℃, the adjustment mechanism is triggered.

[0046] Adjustment strategy: When the temperature is higher than the set value, the PID control algorithm is used to reduce the power of the heating element in proportion to the degree of deviation. For example, the power is reduced by 5% for every 1°C deviation. When the temperature is lower than the set value, the power of the heating element is increased in proportion. For example, the power is increased by 5% for every 1°C deviation. At the same time, the heating time is dynamically adjusted according to the different heating stages. In the first stage, the heating rate is 10°C / min. If the temperature deviation is large, the heating time of this stage is appropriately shortened or extended based on the power adjustment. The adjustment range is 1 minute each time. The system continuously monitors and adjusts to ensure accurate temperature control during the entire gradient heating process.

[0047] Example 2

[0048] like Figure 1 As shown, a brazing process for connecting alumina ceramic and titanium metal with a low-activated brazing filler metal comprises the following steps:

[0049] S1. The surface of alumina ceramic to be welded is subjected to magnetron sputtering titanium coating, the sputtering power is 150W, the argon pressure is 1.5Pa, the film thickness is 5μm, and the coating is subjected to inert gas annealing treatment, the annealing temperature is 550℃, the holding time is 30min, the protective gas for inert gas annealing treatment is argon, the gas flow rate is 50sccm, and the grain size of the film layer after annealing is 200nm;

[0050] S2. The surface of the titanium substrate was subjected to laser microtexturing to form a periodic groove structure with a depth of 50 μm, and then the oxide film was removed by ultrasonic cleaning using a mixed solution of hydrofluoric acid and nitric acid. The groove spacing of the laser microtexturing was 150 μm, and the ratio of the groove width to the depth was 1:3. The volume ratio of the mixed solution was hydrofluoric acid: nitric acid: deionized water = 1:3:6, the ultrasonic cleaning power was 400 W, and the time was 15 min.

[0051] S3. Aluminum-based low-activation solder is used, whose composition is Al 97.65wt.%, Mg 2.8wt.%, Cr 0.35wt.%, and the purity is ≥99%. The solder is prefabricated into a foil with a thickness of 0.5mm, and the surface of the solder foil is doped with 0.1wt.% of rare earth element Ce by ion implantation, and the doping depth is 0.1-0.5μm; the microstructure of the aluminum-based low-activation solder is a nanocrystalline structure, the grain size is ≤100nm, and the Mg2Si and CrAl7 precipitation phases are evenly distributed at the grain boundaries;

[0052] S4. The coated alumina ceramic, the metal titanium substrate and the brazing foil are assembled in sequence to form a laminated structure of alumina ceramic / brazing material / titanium substrate / brazing material / alumina ceramic, and a pre-tightening pressure of 2 MPa is applied. The pre-tightening pressure is achieved by a shape memory alloy fixture. The fixture undergoes phase change and shrinkage at the brazing temperature, and the pressure is dynamically adjusted to ±5% of the set value;

[0053] S5. Gradual heating is carried out in a vacuum brazing furnace: in the first stage, the temperature is increased to 400℃ at 15℃ / min and kept at this temperature for 20min to eliminate interface stress; in the second stage, the temperature is increased to 790℃ at 8℃ / min and kept at this temperature for 60min, and the vacuum degree is ≤1×10-3Pa; in the third stage, the temperature is slowly cooled to below 200℃ at 5℃ / min and then cooled with the furnace. During the holding stage, an alternating magnetic field is applied with a magnetic field strength of 200mT and a frequency of 10kHz.

[0054] After brazing, the joint was aged at 250°C for 8 hours, and then cooled to room temperature at a rate of ≤10°C / min. Figure 3 As shown, there are no cracks;

[0055] During the gradient heating stage, infrared thermal imaging is used to monitor the interface temperature distribution in real time, with the temperature uniformity deviation ≤±5°C, and the heating rate is dynamically adjusted through a feedback system.

[0056] An adaptive control algorithm is introduced to perform gradient temperature rise in a vacuum brazing furnace, as follows:

[0057] Data collection: Use an infrared thermal imager to collect interface temperature distribution data at a frequency of once per second to obtain temperature values ​​at multiple temperature measurement points.

[0058] Comparison judgment: Compare the collected temperature of each temperature measurement point with the preset temperature uniformity deviation range (≤±5℃). If the temperature of a certain point deviates from the set temperature by more than 5℃, the adjustment mechanism is triggered.

[0059] Adjustment strategy: When the temperature is higher than the set value, the PID control algorithm is used to reduce the power of the heating element in proportion to the degree of deviation. For example, the power is reduced by 5% for every 1°C deviation. When the temperature is lower than the set value, the power of the heating element is increased in proportion. For example, the power is increased by 5% for every 1°C deviation. At the same time, the heating time is dynamically adjusted according to the different heating stages. In the first stage, the heating rate is 15°C / min. If the temperature deviation is large, the heating time of this stage is appropriately shortened or extended based on the power adjustment. The adjustment range is 3 minutes each time. The system continuously monitors and adjusts to ensure accurate temperature control during the entire gradient heating process.

[0060] Example 3

[0061] like Figure 1As shown, a brazing process for connecting alumina ceramic and titanium metal with a low-activated brazing filler metal comprises the following steps:

[0062] S1. The surface of alumina ceramic to be welded is subjected to magnetron sputtering titanium coating, the sputtering power is 100W, the argon pressure is 1Pa, the film thickness is 2μm, and the coating is subjected to inert gas annealing treatment, the annealing temperature is 450℃, the holding time is 20min, the protective gas for inert gas annealing treatment is argon, the gas flow rate is 35sccm, and the grain size of the film layer after annealing is 100nm;

[0063] S2. The surface of the titanium substrate was subjected to laser microtexturing to form a periodic groove structure with a depth of 30 μm, and then the oxide film was removed by ultrasonic cleaning using a mixed solution of hydrofluoric acid and nitric acid. The groove spacing of the laser microtexturing was 100 μm, and the ratio of the groove width to the depth was 1:2. The volume ratio of the mixed solution was hydrofluoric acid: nitric acid: deionized water = 1:3:6, the ultrasonic cleaning power was 300 W, and the time was 10 min.

[0064] S3. Aluminum-based low-activation solder is used, whose composition is Al 97.2wt.%, Mg 2.5wt.%, Cr 0.25wt.%, and the purity is ≥99%. The solder is prefabricated into a foil with a thickness of 0.2mm, and the surface of the solder foil is doped with 0.05wt.% of rare earth element Y by ion implantation, and the doping depth is 0.3μm; the microstructure of the aluminum-based low-activation solder is a nanocrystalline structure, the grain size is ≤100nm, and the Mg2Si and CrA l7 precipitation phases are evenly distributed at the grain boundaries;

[0065] S4. The coated alumina ceramic, the metal titanium substrate and the brazing material foil are assembled in sequence to form a laminated structure of alumina ceramic / brazing material / titanium substrate / brazing material / alumina ceramic, and a pre-tightening pressure of 1 MPa is applied. The pre-tightening pressure is achieved by a shape memory alloy fixture. The fixture undergoes phase change and shrinkage at the brazing temperature, and the pressure is dynamically adjusted to ±5% of the set value;

[0066] S5. Gradual heating is carried out in a vacuum brazing furnace: in the first stage, the temperature is increased to 350℃ at 12℃ / min and kept at this temperature for 15min to eliminate interface stress; in the second stage, the temperature is increased to 750℃ at 6℃ / min and kept at this temperature for 30min, and the vacuum degree is ≤1×10-3Pa; in the third stage, the temperature is slowly cooled to below 200℃ at 4℃ / min and then cooled with the furnace. During the holding stage, an alternating magnetic field is applied with a magnetic field strength of 100mT and a frequency of 5kHz.

[0067] After brazing, the joint was aged at 200 °C for 5 h, and then cooled to room temperature at a rate of ≤10 °C / min to obtain the brazed alumina ceramic / titanium sample. Figure 4Shown is the microstructure morphology of the alumina ceramic / metal titanium sample, which has no cracks.

[0068] During the gradient heating stage, infrared thermal imaging is used to monitor the interface temperature distribution in real time, with the temperature uniformity deviation ≤±5°C, and the heating rate is dynamically adjusted through a feedback system.

[0069] In this process of gradient heating, an adaptive control algorithm is introduced, as follows:

[0070] Data collection: Use an infrared thermal imager to collect interface temperature distribution data at a frequency of once per second to obtain temperature values ​​at multiple temperature measurement points.

[0071] Comparison judgment: Compare the collected temperature of each temperature measurement point with the preset temperature uniformity deviation range (≤±5℃). If the temperature of a certain point deviates from the set temperature by more than 5℃, the adjustment mechanism is triggered.

[0072] Adjustment strategy: When the temperature is higher than the set value, the PID control algorithm is used to reduce the power of the heating element in proportion to the degree of deviation. For example, the power is reduced by 5% for every 1°C deviation. When the temperature is lower than the set value, the power of the heating element is increased in proportion. For example, the power is increased by 5% for every 1°C deviation. At the same time, the heating time is dynamically adjusted according to the different heating stages. In the first stage, the heating rate is 12°C / min. If the temperature deviation is large, the heating time of this stage is appropriately shortened or extended based on the power adjustment. The adjustment range is 2 minutes each time. The system continuously monitors and adjusts to ensure accurate temperature control during the entire gradient heating process.

[0073] Example 4

[0074] like Figure 1 As shown, a brazing process for connecting alumina ceramic and titanium metal with a low-activated brazing filler metal comprises the following steps:

[0075] S1. The surface of alumina ceramic to be welded is subjected to magnetron sputtering titanium coating, the sputtering power is 120W, the argon pressure is 1.3Pa, the film thickness is 4.5μm, and the coating is subjected to inert gas annealing treatment, the annealing temperature is 520℃, the holding time is 28min, the protective gas for inert gas annealing treatment is argon, the gas flow rate is 45sccm, and the grain size of the film layer after annealing is 180nm;

[0076] S2. The surface of the titanium substrate was subjected to laser microtexturing to form a periodic groove structure with a depth of 45 μm, and then the oxide film was removed by ultrasonic cleaning using a mixed solution of hydrofluoric acid and nitric acid. The groove spacing of the laser microtexturing was 140 μm, and the ratio of the groove width to the depth was 1:2.5. The volume ratio of the mixed solution was hydrofluoric acid: nitric acid: deionized water = 1:3:6, the ultrasonic cleaning power was 350 W, and the time was 13 min.

[0077] S3. Aluminum-based low-activation solder is used, whose composition is Al97.45 wt.%, Mg 2.6 wt.%, Cr0.20 wt.%, and the purity is ≥99%. The solder is prefabricated into a foil with a thickness of 0.45 mm. The surface of the solder foil is doped with 0.09 wt.% of rare earth element Y by ion implantation, and the doping depth is 0.2 μm. The microstructure of the aluminum-based low-activation solder is a nanocrystalline structure with a grain size of ≤100 nm, and Mg2Si and CrAl7 precipitates are evenly distributed at the grain boundaries;

[0078] S4. The coated alumina ceramic, the metal titanium substrate and the brazing material foil are assembled in sequence to form a laminated structure of alumina ceramic / brazing material / titanium substrate / brazing material / alumina ceramic, and a pre-tightening pressure of 1.8 MPa is applied. The pre-tightening pressure is achieved by a shape memory alloy fixture. The fixture undergoes phase change and shrinkage at the brazing temperature, and the pressure is dynamically adjusted to ±5% of the set value;

[0079] S5. Gradual heating is carried out in a vacuum brazing furnace: in the first stage, the temperature is increased to 380℃ at 13℃ / min and kept for 18min to eliminate interface stress; in the second stage, the temperature is increased to 720℃ at 7℃ / min and kept for 40min, and the vacuum degree is ≤1×10-3Pa; in the third stage, the temperature is slowly cooled to below 200℃ at 3.5℃ / min and then cooled with the furnace. During the holding stage, an alternating magnetic field is applied with a magnetic field strength of 175mT and a frequency of 9kHz.

[0080] After brazing, the joint was aged at 220°C for 7 hours, and then cooled to room temperature at a rate of ≤10°C / min. Figure 5 As shown, there are no cracks.

[0081] During the gradient heating stage, infrared thermal imaging is used to monitor the interface temperature distribution in real time, with the temperature uniformity deviation ≤±5°C, and the heating rate is dynamically adjusted through a feedback system.

[0082] In the process of gradient heating in the vacuum brazing furnace, an adaptive control algorithm is introduced, as follows:

[0083] Data collection: Use an infrared thermal imager to collect interface temperature distribution data at a frequency of once per second to obtain temperature values ​​at multiple temperature measurement points.

[0084] Comparison judgment: Compare the collected temperature of each temperature measurement point with the preset temperature uniformity deviation range (≤±5℃). If the temperature of a certain point deviates from the set temperature by more than 5℃, the adjustment mechanism is triggered.

[0085] Adjustment strategy: When the temperature is higher than the set value, the PID control algorithm is used to reduce the power of the heating element in proportion to the degree of deviation. For example, the power is reduced by 5% for every 1°C deviation. When the temperature is lower than the set value, the power of the heating element is increased in proportion. For example, the power is increased by 5% for every 1°C deviation. At the same time, the heating time is dynamically adjusted according to the different heating stages. In the first stage, the heating rate is 14°C / min. If the temperature deviation is large, the heating time of this stage is appropriately shortened or extended based on the power adjustment. The adjustment range is 2.5 minutes each time. The system continuously monitors and adjusts to ensure accurate temperature control during the entire gradient heating process.

[0086] The present invention can enhance the wettability of ceramics and solder by magnetron sputtering titanium film on the surface of alumina ceramic to be welded, and refine the film grains by inert gas annealing after plating, thereby improving the stability and bonding strength of the film; the periodic groove structure formed by laser microtexturing on the surface of the metal titanium substrate increases the contact area with the solder, improves the mechanical interlocking effect, and enhances the connection strength. The use of aluminum-based low-activation solder with a specific composition, its nanocrystalline structure and the uniformly distributed precipitation phase at the grain boundary improve the strength, toughness and corrosion resistance of the solder; the surface of the solder foil is doped with rare earth elements Y or Ce to further improve the wettability, fluidity and interface reaction of the solder, thereby improving the joint performance.

[0087] It is worth mentioning that the gradient heating method can effectively eliminate interface stress and avoid problems such as material deformation and cracking caused by rapid temperature changes; applying an alternating magnetic field during the insulation stage can promote the diffusion of solder atoms, improve the uniformity of joint organization, and improve the strength and density of the joint; using infrared thermal imaging to monitor the interface temperature distribution in real time and dynamically adjust the heating rate to ensure temperature uniformity and improve the stability of brazing quality. The pre-tightening pressure is achieved by using shape memory alloy fixtures, and the pressure can be dynamically adjusted according to demand at the brazing temperature to ensure stable pressure during the brazing process, ensure close contact between the solder and the base material, and improve the connection quality. Aging treatment after brazing can eliminate residual stress, improve joint organization and performance, and improve the strength, hardness and corrosion resistance of the joint, so that the joint can meet the needs of more complex working conditions.

[0088] The above specific embodiments are only several optional embodiments of the present invention. Based on the technical solutions of the present invention and the relevant inspirations of the above embodiments, those skilled in the art can make various alternative improvements and combinations to the above specific embodiments.

Claims

1. A brazing process for connecting alumina ceramics and titanium metal with low-activated brazing filler metal, characterized in that: The following steps are involved: S1. The surface of alumina ceramic to be welded is subjected to magnetron sputtering titanium coating, the sputtering power is 80-150W, the argon pressure is 0.5-1.5Pa, the film thickness is 0.5-5μm, and after coating, it is annealed by inert gas, the annealing temperature is 400-550℃, and the holding time is 10-30min; S2. The surface of the titanium substrate is subjected to laser microtexturing to form a periodic groove structure with a depth of 10-50 μm, and then the oxide film is removed by ultrasonic cleaning using a mixed solution of hydrofluoric acid and nitric acid; S3. A low-activated aluminum-based solder having a composition of 96.8-97.65wt.% Al, 2.2-2.8wt.% Mg, 0.15-0.35wt.%, and a purity of ≥99%, and the solder is preformed into a foil having a thickness of 0.02-0.5mm; S4. The coated alumina ceramic, the titanium substrate and the brazing foil are assembled in sequence to form a laminated structure of alumina ceramic / brazing material / titanium substrate / brazing material / alumina ceramic, and a preload pressure of 0.5-2MPa is applied; S5. Perform a gradient temperature increase in a vacuum brazing furnace: in the first stage, the temperature is increased to 300-400°C at 10-15°C / min and kept at this temperature for 10-20min to eliminate the interface stress; In the second stage, the temperature is raised to 690-790°C at 5-8°C / min, kept at this temperature for 2-60min, and the vacuum degree is ≤1×10-3Pa; in the third stage, the temperature is slowly cooled to below 200°C at 3-5°C / min and then cooled with the furnace.

2. The brazing process according to claim 1, characterized in that: The protective gas for the inert gas annealing treatment in step S1 is argon or helium, the gas flow rate is 20-50 sccm, and the grain size of the film layer after annealing is 50-200 nm.

3. The brazing process according to claim 1, characterized in that: The groove pitch of the laser microtexturing in step S2 is 50-150 μm, and the ratio of groove width to depth is 1:1.5-1:

3.

4. The brazing process according to claim 1, characterized in that: In step S3, the surface of the solder foil is doped with 0.01-0.1 wt.% of rare earth element Y or Ce by ion implantation, and the doping depth is 0.1-0.5 μm.

5. The brazing process according to claim 1, characterized in that: In the step S5, an alternating magnetic field is applied during the heat preservation stage, with a magnetic field strength of 50-200 mT and a frequency of 1-10 kHz.

6. The brazing process according to claim 1, characterized in that: After the brazing is completed, the joint is subjected to aging treatment, the aging temperature is 150-250° C., the insulation time is 2-8 hours, and then cooled to room temperature at a rate of ≤10° C. / min.

7. The brazing process according to claim 1, characterized in that: In step S4, the pre-tightening pressure is achieved by a shape memory alloy fixture, and the fixture undergoes phase change and shrinkage at the brazing temperature, and the pressure is dynamically adjusted to ±5% of the set value.

8. The brazing process according to claim 1, characterized in that: The microstructure of the aluminum-based low-activation solder is a nanocrystalline structure, the grain size is ≤100nm, and Mg2Si and CrAl7 precipitation phases are evenly distributed at the grain boundaries.

9. The brazing process according to claim 1, characterized in that: The volume ratio of the mixed solution in step S2 is hydrofluoric acid: nitric acid: deionized water = 1:3:6, the ultrasonic cleaning power is 200-400W, and the time is 5-15min.

10. The brazing process according to claim 1, characterized in that: In the gradient heating stage, the interface temperature distribution is monitored in real time by infrared thermal imaging, the temperature uniformity deviation is ≤±5°C, and the heating rate is dynamically adjusted by a feedback system.

Citation Information

Patent Citations

  • Method of Brazing ceramic and ceramic-based composite material with titan alloy

    CN101333116A

  • Aluminum oxide ceramic metallization method used for brazing

    CN105330340A

  • Direct aluminum or aluminum alloy brazing method for aluminum oxide ceramics

    CN105436643A

  • Brazing filler metal for brazing aluminum oxide ceramics with oxygen-free copper, and preparation and brazing method

    CN106475707A

  • Preparation method of aluminum nitride ceramic copper-clad plate

    CN108033810A

Cited By

  • High-performance insulating ceramic sealing method for neutron tube

    CN121574004A

  • Sapphire-kovar alloy connector and welding method thereof

    CN121649495A

  • Welding process of high-strength cutter alloy steel and ceramic composite layer

    CN121946000A